Exploitation reduction and conservation of local beef cattle as a result of demand for beef through massive artificial insemination programs in Indonesia - Firman, Achmad (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Indonesian Ministry of Agriculture has made a breakthrough in increasing the cattle population to reduce supply inequality through a SIWAB/SIKOMANDAN program. The program focuses on massive artificial insemination and is supported other activities, namely feed aid, animal health, veterinary public health, and community services. The purpose of the study was to determine the conservation of local cattle genetic resources, increasing population, and economic valuation. The research data was collected from Directorate General Livestock and Health (DGLH) for four years. Mathematics models were used to analyze the target and realization the number of frozen semen distribution, acceptor cows, pregnant cows, and calves born. The incremental capital-output ratio (ICOR) model was used to determine the economic valuation. The results show that the program could conserve local cattle, the number of pregnant cows was 8.17 million heads (87.84%), and the number of calves born was 7,040,160 heads or more than 100% of the target for four years as many as 7,040,000 cattle. The average service per-conception (S/C) value was 2.06 or in the normal range. The economic valuation of government investment could generate economic value added marked with an ICOR < 1 or efficient investment.